Current‐Controlled Topological Magnetic Transformations in a Nanostructured Kagome Magnet (Adv. Mater. 33/2021). Issue 33 (17th August 2021) - Wei, Wensen; Tang, Jin; Wu, Yaodong; Wang, Yihao; Jiang, Jialiang; Li, Junbo; Soh, Yona; Xiong, Yimin; Tian, Mingliang; Du, Haifeng
Abstract : Spintronic Devices Writing and erasing operations in promising skyrmion‐bubble‐based spintronic devices are expected to be achieved by electric‐controlled skyrmion–bubble transformations. In article number 2101610, Jin Tang, Haifeng Du, and co‐workers realize current‐controlled topological skyrmion–bubble magnetic transformations in a reversible way by tuning the nanosecond pulsed current density on the order of 10 6 A cm −2 .